POLYMERIZATION FLUID, PROCESS FOR PRODUCTION THEREOF, TRANSPARENT FILM MADE FROM THE POLYMERIZATION FLUID, AND TRANSPARENT ELECTRODE - ATOBE, MAHITO; MACHIDA, KENJI; TAKEDA, SEKIHIRO; NAKABAYASHI, KOJI (2013)
Disclosed is a polymerization fluid for electropolymerization which exhibits a reduced environmental burden and excellent economic efficiency and which can yield a conductive polymer film that has high conductivity and that is dense and highly transparent. The polymerization fluid includes at least one monomer selected from the group consisting of 3,4-disubstituted thiophenes which is dispersed as oil drops in surfactant-free water, and the polymerization fluid is transparent. The polymerization fluid can be produced by a method which includes: an addition step of adding the monomer to surfactant-free water to prepare a phase separation fluid where water and the monomer are phase-separated; a first dispersion step of irradiating the phase separation fluid with ultrasonic waves to make the monomer dispersed in the form of oil drops and thus prepare an opaque dispersion, and a second dispersion step of irradiating the opaque dispersion with ultrasonic waves having a frequency higher than that of the ultrasonic waves used in the first dispersion step to reduce the mean size of the oil drops of the monomer and thus prepare a transparent dispersion.